1997
DOI: 10.3354/meps157001
|View full text |Cite
|
Sign up to set email alerts
|

Significance of bacteria in the flux of organic matter in the tidal creeks of the mangrove ecosystem of the Indus River delta, Pakistan

Abstract: We studied bacterial blomass and production in 3 t~d a l creeks (Isaro, Gharo and Ph~ttl Creeks) in the mangrove forests in the Indus R~ver delta, Pakistan, to assess the signif~cance of bacteria-mediated carbon fluxes in the creek ecosystem. Bacterial biomass, bacterial carbon production (BCP) and primary productivity (PP) were measured periodically for over a year during 1991-92. BCP was high, generally 50 to 300 pg C 1-' d-l. Despite such high BCP, bacterial abundance remained between 1 X 106 ml-' and 4 X 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
50
0
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 18 publications
8
50
0
5
Order By: Relevance
“…The material produced, mainly leaves, enriches the bottom litter (Fleming et al 1990). The decompostion rate of the litter and the quality of the resulting particulate organic matter and nutrients may depend on which mangrove species the leaves come from (Tam et al 1990), on biotic factors such as bacterial activity (Bano et al 1997), and on edaphic effects such as tidal range and temperature (Slim et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The material produced, mainly leaves, enriches the bottom litter (Fleming et al 1990). The decompostion rate of the litter and the quality of the resulting particulate organic matter and nutrients may depend on which mangrove species the leaves come from (Tam et al 1990), on biotic factors such as bacterial activity (Bano et al 1997), and on edaphic effects such as tidal range and temperature (Slim et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The abundance of PAB in the Mandovi estuary was 2 to 4 times more than that reported in temperate waters (Hoch et al 1995, Berger et al 1996) and the adjacent Zuari estuary (De Souza et al 2003). However, it was lower than the highly organic rich Hudson and Indus River delta estuaries (Bano et al 1997, Sanudo-Wilhelmy & Taylor 1999. Although the quantitative POM content of the particles was low, its quality was high with a POC:PON ratio of 5.5 to 7.3.…”
mentioning
confidence: 73%
“…Fukuda et al (1998) concluded from their study that a factor of 30.2 ± 12.3 fg C cell -1 would be applicable for coastal bacterial assemblages. In a study on estuaries from Indian regions, Bhaskar & Bhosle (2008) ) in Pakistan (Bano et al 1997). Earlier studies (Simon et al 1990, Smith et al 1992, Grossart & Simon 1998) measured aggregate-associated bacterial production by pooling several aggregates.…”
mentioning
confidence: 99%
“…Ainsi, la dégradation du matériel végétal dans les écosystèmes de mangroves produit des détritus qui peuvent être définis comme de la matière organique en phase de décomposition. Les détritus sont riches en énergie et contiennent une grande population microbienne active (Bano et al, 1997). En plus des bactéries et des champignons, d'autres organismes peuvent également coloniser le matériel végétal et contribuer à la formation des détritus (D'Croz et al, 1989).…”
Section: Transformation De La Matiere Organique Par Les Microorganismesunclassified
“…Elles traitent la plupart des flux d'énergie et de nutriments, et agissent comme un puits de carbone. Par exemple, dans les écosystèmes de mangroves semi-arides, les bactéries sont attachés aux particules des sédiments et transforment la plupart des nutriments de l'écosystème (Bano et al, 1997). En consommant du carbone organique dissous présent dans les eaux interstitielles, les populations bactériennes dans les sédiments de mangrove empêchent l'exportation de cette forme de carbone vers les écosystèmes adjacents (Alongi et al, 1989).…”
Section: Transformation Des Nutriments Par Les Microorganismes Dans Uunclassified